Single-particle cryo-EM using alignment by classification (ABC): the structure of Lumbricus terrestris haemoglobin. (2017) - Afanasyev, Pavel; Seer-Linnemayr, Charlotte; Ravelli, Raimond B. G.; Matadeen, Rishi; Carlo, Sacha De; Alewijnse, Bart
No abstract available